Mechanism of electric-pulse-induced resistance switching in manganites - Quintero, Mariana Beatriz (2007)
We investigate the electric-pulse-induced resistance switching in manganite systems. We find a "complementarity" effect where the contact resistance of electrodes at opposite ends show variations of opposite sign and is reversible. The temperature dependence of the magnitude of the effect reveals a dramatic enhancement at a temperature T*, below the metal-insulator transition. We qualitatively capture these features with a theoretical model, providing evidence for the physical mechanism of the resistance switching. We argue that doping control of the electronic state of the oxide at the interfaces is the mechanism driving the effect. © 2007 The American Physical Society.